Associations Between Food Insecurity and Common Mental Health Problems Among Reproductive-Aged Women in Kabul-Afghanistan - Zahidi, Fawzia; Khalid, Madiha; Surkan, Pamela J.; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Background: Food insecurity has been linked to poor health outcomes, however this relationship is poorly understood among women of reproductive age. Therefore, we investigated the relationship between food insecurity and common mental health problems (CMHPs) in this population of women in Kabul, Afghanistan. ‎ Method: A cross-sectional study was conducted with 421 women of reproductive age from four health centers located in four randomly selected zones in the city of Kabul. We used the United State Department of Agriculture (USDA) food-insecurity questionnaire, multiple 24-hour recall for dietary intake, the Depression, the Anxiety and Stress Scale (DASS-21) to assess major mental health problems, and the International Physical Activity Questionnaire (IPAQ) to assess physical activity. Result: Food insecurity affected 69.6% of reproductive-aged women. In total, 44.9%, 10.9%, and 13.9% of food-insecure participants had food insecurity without hunger, food insecurity with hunger, and food insecurity with severe hunger, respectively. Depression, anxiety, and stress were prevalent among food-insecure participants at 89.4%, 90.8%, and 85.7%, respectively. ‎Food insecurity was associated with depression (OR= 4.9, 95% CI: 2.7- 8.9), anxiety (OR= 4.7, 95% CI: 2.5-8.8), and stress (OR=3.8, 95% CI: 2.2-6.7). Women's household ownership, family size, and hypertension, on the other hand, were not associated with food insecurity. ‎ Conclusion: This study found food insecurity was associated with CMHPs among a sample of reproductive-aged women in Kabul, Afghanistan. Further longitudinal studies are needed to confirm these findings.